2016
DOI: 10.7324/japs.2016.60606
|View full text |Cite
|
Sign up to set email alerts
|

Production of antioxidant xylooligosaccharides from lignocellulosic materials using Bacillus amyloliquifaciens NRRL B-14393 xylanase

Abstract: The present study aimed to evaluate the enzymatic production of XOS, antioxidant activities together with total phenolic contents from different lignocellulosic materials and birchwoodxylan using both crude and pure forms of Bacillus amyloliquifaciens NRRL B-14393 xylanase respectively. The mode of action of the pure xylanase was studied by HPLC and the end products analysis of birchwoodxylan revealed that xylose, xylobiose and xylotriose were the only end products. The resulted XOS mixture exhibited potent an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 14 publications
(23 reference statements)
0
8
0
Order By: Relevance
“…Although the antioxidant capacity of XOS produced by xylanases has been reported in several works, to our knowledge, differences in the antioxidant effect of XOS obtained by different families of xylanases has not been described previously. The XOS described in literature come from different raw materials such as sugarcane bagasse (Bian et al, 2013;Mandelli et al, 2014), corncob (Gowdhaman & Ponnusami, 2015), garlic straw (Kallel, Driss, Chaabouni, & Ghorbel, 2014), wheat bran (Lasrado & Gudipati, 2014), wheat aleurone (Malunga & Beta, 2015), sunflower stalk and wheat straw (Akpinar, Erdogan, et al, 2010), or agricultural residues (Rashad et al, 2016 Rao & Muralikrishna (2006) showed that the presence of sugars with uronyl or acetyl groups impart strong antioxidant activity to cereal polysaccharides. It has been also reported that carboxyl groups increase antioxidant activity of cell wall polysaccharides (Pristov, Mitrovi, & Spasojevi, 2011).…”
Section: Xos_30 Xos_10mentioning
confidence: 99%
See 1 more Smart Citation
“…Although the antioxidant capacity of XOS produced by xylanases has been reported in several works, to our knowledge, differences in the antioxidant effect of XOS obtained by different families of xylanases has not been described previously. The XOS described in literature come from different raw materials such as sugarcane bagasse (Bian et al, 2013;Mandelli et al, 2014), corncob (Gowdhaman & Ponnusami, 2015), garlic straw (Kallel, Driss, Chaabouni, & Ghorbel, 2014), wheat bran (Lasrado & Gudipati, 2014), wheat aleurone (Malunga & Beta, 2015), sunflower stalk and wheat straw (Akpinar, Erdogan, et al, 2010), or agricultural residues (Rashad et al, 2016 Rao & Muralikrishna (2006) showed that the presence of sugars with uronyl or acetyl groups impart strong antioxidant activity to cereal polysaccharides. It has been also reported that carboxyl groups increase antioxidant activity of cell wall polysaccharides (Pristov, Mitrovi, & Spasojevi, 2011).…”
Section: Xos_30 Xos_10mentioning
confidence: 99%
“…In fact, high antioxidant activity has been reported in water-soluble arabinoxylans (feraxans) (Rao & Muralikrishna, 2006), isolated from rice and ragi. The phenolic content of oligosaccharides has been proposed to have an important effect in antioxidant activity (Bijalwan, Ali, Kesarwani, Yadav, & Mazumder, 2016;Rashad et al, 2016). On the other hand, in beechwood and birchwood XOS, since they do not contain ferulic acid, the main reason of their antioxidant capacity was the presence of methyl glucuronic acid ramifications.…”
Section: Antioxidant Activity Of Xos From Birchwood and Oat Spelt Xylansmentioning
confidence: 99%
“…The supernatant contained crude enzymes of hemicellulase. Xylanase activity was measured using Nelson and Somogyi method [17,18]. One unit (U) of xylanase activity is defined as the number of enzymes needed to produce one milliliter of reducing sugars (xilose) per minute at 37 ºC.…”
Section: Screening Of Hemicellulolytic Bacteria Based On Hydrolysis O...mentioning
confidence: 99%
“…During both acute and chronic diseases in humans, the abundance of free radicals usually increases. Several notable studies demonstrated that XOS had exhibited strong antioxidant and free radical scavenging activity, thus suggesting a potential use in biomedical applications ( 52 , 53 ). The scavenging ability of XOS was shown to be dose-dependent ( 54 ), and this potential is likely attributable to efficient release of phenolic compounds and transfer of hydrogen atoms from the phenolic compounds to free radicals ( 55 ).…”
Section: Xos Application To Human Healthmentioning
confidence: 99%